Bergey's Manual of Systematics of Archaea and Bacteria 2019
DOI: 10.1002/9781118960608.gbm00485.pub2
|View full text |Cite
|
Sign up to set email alerts
|

H aloferax

Abstract: Ha.lo.fe'rax. Gr. n. hals, halos salt; L. neut. adj. ferax fertile; N.L. neut. n. Haloferax salt (requiring) and fertile. Euryarchaeota / Halobacteria / Haloferacales / Haloferacaceae / Haloferax The genus Haloferax is classified within the family Haloferacaceae and the order Haloferacales , in the class Halobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…asiatica and has a low amount in Hf. mediterranei, which are extreme salt-adapted strains (Merino et al, 2019) that have the highest optimum NaCl concentrations (3.4 M and 4.0 M, respectively) among the 7 strains (Figure 3C) (Hezayen et al, 2001;Ventosa et al, 2009). Accordingly, we inferred that strains thriving under such extreme salt conditions may not favor the production of bacterioruberin.…”
Section: Lipidomic Potential For Phylogenetic Classification Of Halob...mentioning
confidence: 85%
See 1 more Smart Citation
“…asiatica and has a low amount in Hf. mediterranei, which are extreme salt-adapted strains (Merino et al, 2019) that have the highest optimum NaCl concentrations (3.4 M and 4.0 M, respectively) among the 7 strains (Figure 3C) (Hezayen et al, 2001;Ventosa et al, 2009). Accordingly, we inferred that strains thriving under such extreme salt conditions may not favor the production of bacterioruberin.…”
Section: Lipidomic Potential For Phylogenetic Classification Of Halob...mentioning
confidence: 85%
“…The annotation results referred to 107 unique lipids, encompassing the majority of lipids previously reported in Halobacteria. These included unsaturated and extended diether core structures; IPLs of PG, Me-PGP, DGD and S-DGD; cardiolipins of both BPG and glycocardiolipins; non-bilayer forming lipids of MK and bacterioruberin (Kamekura and Kates, 1999;Ventosa et al, 1999;Hezayen et al, 2001;Sprott et al, 2003;Xu et al, 2007;Tapingkae et al, 2008;Minegishi and Kamekura, 2009;Ventosa et al, 2009;Elling et al, 2016).…”
Section: Enhancing the Lipidomic Capability Of Chemotaxonomy By Netwo...mentioning
confidence: 99%
“…Interestingly, H. salinarum proteome was destabilized by chaotropic salts, MgCl 2 as well as (per)chlorate salts. By comparison, H. sodomense and H. volcanii optimally grow at lower NaCl concentrations (McGenity & Grant, 2015; Ventosa et al, 2015) and showed proteomes that are the least destabilized and even distinctively stabilized in some occasions by chaotropic salts. Moreover, H. mediterranei has the largest NaCl concentration range compatible with growth and tolerates both high and low NaCl concentrations (Oren, 2017; Oren & Hallsworth, 2014) and showed a proteome with intermediary behaviour in our measurements.…”
Section: Discussionmentioning
confidence: 99%